Effect of tobacco use on cadmium accumulation in the oral keratinized mucosa - Samed Satir; Dogan Ilgaz Kaya; Sumeyye Celik Ozsoy (BMC, 2024)
Abstract Background This cross-sectional study aimed to evaluate the effect of tobacco use on the accumulation of cadmium (Cd), a carcinogenic element, in the oral keratinized mucosa (OKM). Methods OKM samples were obtained by standard punch biopsy from nonsmokers (n = 19) and smokers (n = 21). Cd analysis was performed using inductively coupled plasma optical emission spectroscopy (ICP-OES). The calibration curve R2 values for three wavelengths (214,439, 226,502, and 228,802 nm) were at the level of 0.9999. The frequency of consumption of foods that are Cd sources, such as seafood, rice, and vegetables, was assessed in all patients. The age, sex, and nutritional habits of all patients and the frequency of tobacco consumption by smokers were recorded. The independent t-test, Mann-Whitney U test, Fisher's exact test, and Spearman correlation test were used for the statistical analyses, and p < 0.05 was considered significant. Results Although the Cd levels in nonsmokers were higher than those in smokers, no statistically significant difference was found (p > 0.05). In smokers, a positive correlation was found between age and Cd level (r = 0.574, p = 0.006). No significant relationship was found between the groups in terms of nutrition or between the frequency of tobacco consumption and Cd accumulation. Conclusion The OKM may not have the characteristic cumulative accumulation in terms of toxic elements. Changes in the turnover rate, keratinization, and apoptotic mechanisms in the OKM with the thermal/chemical effects of tobacco may be responsible for the difference in Cd accumulation. Trial registration number TCTR20230206001/06 Feb 2023 (TCTR: Thai Clinical Trials Registry).